2002
DOI: 10.2307/3761799
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Taxonomic Placement of Rhizoctonia-like Endophytes from Orchid Roots

Abstract: Y l i "), O 'LO02 I]\ Tlie Xf)cological Societ~ of .-\mcrica. L.a~vrcncc. liS 6GO4+88Yi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 8 publications
2
36
1
4
Order By: Relevance
“…As diferenças nas dimensões das células monilioides, tanto na largura (LCM) quanto no comprimento (CCM) (Quadro 2), confirmaram as diferenças observadas no aspecto da colônia e na morfologia das células monilioides. As características qualitativas da colônia, o diâmetro da hifa vegetativa e a morfologia e a dimensão das células monilioides são importantes na identificação dos isolados de fungos rizoctonioides em nível de gênero e de espécie (Currah & Zelmer, 1992;Zelmer & Currah, 1995;Currah & Zelmer, 1997;Shan et al, 2002;Pereira et al, 2003), entretanto a identificação em nível de espécie é mais segura quando subsidiada pela avaliação de características moleculares, tais como sequência da região ITS (internal transcribed spacer) do rDNA ou da região mtLSU (mitochondrial large subunit) (Taylor & Bruns, 1999;Taylor et al, 2002).…”
Section: Resultsunclassified
“…As diferenças nas dimensões das células monilioides, tanto na largura (LCM) quanto no comprimento (CCM) (Quadro 2), confirmaram as diferenças observadas no aspecto da colônia e na morfologia das células monilioides. As características qualitativas da colônia, o diâmetro da hifa vegetativa e a morfologia e a dimensão das células monilioides são importantes na identificação dos isolados de fungos rizoctonioides em nível de gênero e de espécie (Currah & Zelmer, 1992;Zelmer & Currah, 1995;Currah & Zelmer, 1997;Shan et al, 2002;Pereira et al, 2003), entretanto a identificação em nível de espécie é mais segura quando subsidiada pela avaliação de características moleculares, tais como sequência da região ITS (internal transcribed spacer) do rDNA ou da região mtLSU (mitochondrial large subunit) (Taylor & Bruns, 1999;Taylor et al, 2002).…”
Section: Resultsunclassified
“…On the other hand, studies based on the AFLP technique, scarcely employed in Rhizoctonia, were based on several aspects related to factors and genes involved in sexual compatibility mechanisms of R. solani (Julián et al, 1999) or investigating genetic diversity of some R. solani AG (Ceresini et al, 2002). Sequencing of ribosomal DNA has been widely employed in the complex during recent years, to reconstruct phylogenetic relationships between the different organisms of the form genus (Boysen et al, 1996;Kuninaga et al, 1997;Roberts, 1999;Salazar et al, 1999Salazar et al, , 2000González et al, 2001González et al, , 2002Pope and Carter, 2001;Shan et al, 2002) or less frequently other regions such as beta-tubuline (González et al, 2003). In the future, molecular approaches should include the sequencing of a broader range of DNA regions (e.g.…”
Section: Molecular Approaches To Study the Form Genusmentioning
confidence: 99%
“…including colony size, colony growth, colour and sclerotia formation (ring at periphery, peripheral or scattered) and texture (smooth or rough). Shan et al (2002) studied cultural morphology and variation, which was found among different isolates including colony colour, growth rate, shape and colony appearance. Moni et al (2015) observed significant variation among different isolates of Rhizoctonia sp.…”
Section: Resultsmentioning
confidence: 99%